Rubber Composites Based on Polar Elastomers with Incorporated Modified and Unmodified Magnetic Filler - Ján Kruželák; Richard Sýkora; Rastislav Dosoudil; Ivan Hudec (Advances in Materials Science and Engineering)
Rubber magnetic composites were prepared by incorporation of unmodified and surface modified strontium ferrite into rubber matrices based on NBR and NBR/PVC. Strontium ferrite was dosed to the rubber matrices in concentration scale ranging from 0 to 100 phr. The main goal was to investigate the influence of the type of ferrite on the curing process, physical-mechanical and magnetic properties of composites. The mutual interactions between the filler and rubber matrices were investigated by determination of cross-link density and SEM analysis. The incorporation of magnetic fillers leads to the increase of cross-link density and remanent magnetic induction of composites. Moreover, the improvement of physical-mechanical properties was achieved in dependence on the content of magnetic fillers. Surface modification of ferrite contributed to the enhancement of adhesion on the interphase filler-rubber. It can be stated that ferrite exhibits reinforcing effect in the composite materials and this reinforcing behavior was emphasized with the increase in polarity of the rubber matrix.